2008
DOI: 10.1128/jb.00790-08
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Active-Site Components of the Putative p -Cresol Methylhydroxylase Membrane Complex from Geobacter metallireducens

Abstract: p-Cresol methylhydroxylases (PCMH) from aerobic and facultatively anaerobic bacteria are soluble, periplasmic flavocytochromes that catalyze the first step in biological p-cresol degradation, the hydroxylation of the substrate with water. Recent results suggested that p-cresol degradation in the strictly anaerobic Geobacter metallireducens involves a tightly membrane-bound PCMH complex. In this work, the soluble components of this complex were purified and characterized. The data obtained suggest a molecular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…This is subsequently transformed to 4-hydroxybenzyl alcohol via a nucleophilic attack of a water molecule at the methide carbon atom, i.e., a formal 1,6-addition of water to the quinone-methide intermediate (25,68). Based on homology, a similar mechanism for p-cresol hydroxylation may be envisioned for Pch from G. metallireducens T (69). It may be assumed that the hydroxyl group plays an integral role in the reaction to allow formation of the quinone-methide intermediate based on electron donation either from one of the lone pairs of the hydroxyl group or from the corresponding oxyanion.…”
Section: Discussionmentioning
confidence: 99%
“…This is subsequently transformed to 4-hydroxybenzyl alcohol via a nucleophilic attack of a water molecule at the methide carbon atom, i.e., a formal 1,6-addition of water to the quinone-methide intermediate (25,68). Based on homology, a similar mechanism for p-cresol hydroxylation may be envisioned for Pch from G. metallireducens T (69). It may be assumed that the hydroxyl group plays an integral role in the reaction to allow formation of the quinone-methide intermediate based on electron donation either from one of the lone pairs of the hydroxyl group or from the corresponding oxyanion.…”
Section: Discussionmentioning
confidence: 99%
“…13). The purification and characterization of the soluble PcmIJ and PcmG components confirmed that p-cresol methylhydroxylase from G. metallireducens has a unique ␣␣Ј␤ 2 -subunit composition, with the ␣ subunit (PcmI) harboring the typical FAD cofactor, which is lacking in the catalytically inactive ␣Ј-subunit (PcmJ), and the ␤-subunit (PcmG) representing a c-type cytochrome (171). In contrast to other aerobic and facultatively anaerobic p-cresol-degrading organisms, G. metallireducens appears to use p-cresol methylhydroxylase for both p-cresol and p-hydroxybenzyl alcohol oxidation in vivo.…”
Section: Vol 73 2009 Anaerobic Biodegradation Of Aromatics 95mentioning
confidence: 96%
“…Although the oxidation of p-hydroxybenzyl alcohol to p-hydroxybenzaldehyde can also be carried out by p-cresol methylhydroxylase, an NAD ϩ -dependent p-hydroxybenzyl alcohol dehydrogenase was supposed to catalyze this reaction in vivo (75,171,183). This oxygen-independent pcresol hydroxylation has also been described for several denitrifying bacteria such as Thauera and Azoarcus strains (239,308) as well as for an Achromobacter strain (162).…”
Section: Vol 73 2009 Anaerobic Biodegradation Of Aromatics 95mentioning
confidence: 98%
See 2 more Smart Citations